Culturing and Scaling up Stem Cells of Dental Pulp Origin Using Microcarriers - Anna Földes (MDPI AG, 2021)
Ectomesenchymal stem cells derived from the dental pulp are of neural crest origin, and as such are promising sources for cell therapy and tissue engineering. For safe upscaling of these cells, microcarrier-based culturing under dynamic conditions is a promising technology. We tested the suitability of two microcarriers, non-porous Cytodex 1 and porous Cytopore 2, for culturing well characterized dental pulp stem cells (DPSCs) using a shake flask system. Human DPSCs were cultured on these microcarriers in 96-well plates, and further expanded in shake flasks for upscaling experiments. Cell viability was measured using the alamarBlue assay, while cell morphology was observed by conventional and two-photon microscopies. Glucose consumption of cells was detected by the glucose oxidase/Clark-electrode method. DPSCs adhered to and grew well on both microcarrier surfaces and were also found in the pores of the Cytopore 2. Cells grown in tissue culture plates (static, non-shaking conditions) yielded 7 × 105 cells/well. In shake flasks, static preincubation promoted cell adhesion to the microcarriers. Under dynamic culture conditions (shaking) 3 × 107 cells were obtained in shake flasks. The DPSCs exhausted their glucose supply from the medium by day seven even with partial batch-feeding. In conclusion, both non-porous and porous microcarriers are suitable for upscaling ectomesenchymal DPSCs under dynamic culture conditions.